« J’avais peur, mais maintenant, c’est chez moi » : parcours de femmes réfugiées en situation monoparentale à Montréal - Marie Fally (Centre Urbanisation Culture Société (UCS) de l'INRS, 2021)
Research Framework: The number of displaced people in the world now stands at 82.4 million. The UN Refugee Agency (UNHCR) remains critical of the low quotas granted to refugees in Canada and since 2018 one of its recommendations has been to prioritize vulnerable populations, in particular single women with children, who are at the heart of this research. In the context of forced migration, being a single mother often rhymes with precarity, instability and socio-economic inequalities, which have all been dramatically multiplied with the pandemic. Objectives: The objective is to examine the strategies these women put into place to anchor themselves in Quebec society, and to face the daily challenges in their lives. Methodology: The article is based on data collected through semi-structured interviews with Montreal-based single refugee mothers. Results: These mothers find themselves juggling between tumultuous emotions, daily challenges, and familial responsibilities. Their journeys illustrate the ways in which resilience and agency intersect in the management of family dynamics as well as in settlement experiences. Conclusions: Family transformations and the challenges of forced migration push refugee mothers to rebuild not only their home, but also their individuality as women and mothers, which challenges the often-reductive perspectives on motherhood and resilience. Contribution: The results presented allow to nuance the concepts of resilience and agency while highlighting their ambivalence and their complexity. They also reveal the ways refugee mothers rebuild their lives after experiencing forced migration.